Analisis Pengaruh Program Subsidi Beras Terhadap Stabilitas Pasokan Dan Harga Pangan di Kota Sorong - Agus Irianto; Yopi M Hehanusa; Siti Hanafiah Bauw; Andi Irwan (Jurnal Online Manajemen ELPEI, 2026)
This study aims to analyze the effect of the rice subsidy program on the stabilization of food supply and prices in Sorong City. Most previous studies on the effectiveness of rice subsidies and food price stabilization policies have been conducted in regions such as Java, Sumatra, and Sulawesi. This research offers a novel contribution by examining the implementation of rice subsidies in Sorong City, an area characterized by distinct geographical and logistical conditions. Distribution patterns, transportation costs, and infrastructure limitations in Southwest Papua generate findings that differ from those identified in other regions. The study employs a qualitative approach combining literature review and field data. Data were collected through interviews with the Food Security Agency, rice distributors, and beneficiary communities, as well as through an analysis of policy documents related to food subsidies. The results indicate that the rice subsidy program plays a significant role in maintaining price stability and ensuring the availability of staple food supplies. However, its effectiveness is still influenced by distribution mechanisms, transparency, and the accuracy of targeting beneficiaries. Improvements in data management systems and distribution monitoring are necessary to enhance the efficiency and fairness of program implementation in the field. This study focuses exclusively on Sorong City as the research location. Although it provides an in-depth overview of rice subsidy implementation in this area, the findings cannot be fully generalized to other districts or municipalities in Southwest Papua or other regions of Eastern Indonesia with different logistical characteristics.